Preliminary phytochemical characterization and in vitro antioxidant and antimicrobial potential screening of an ayurvedic drug combination Panchatikta - CM, Harinarayanan; M, Deepak; SP, Geetha; Kumar, Anupam (Plant Science Today, 2024)
Panchatikta is an Ayurvedic drug combination of 5 bitter-tasting drugs, namely Azadirachta indica, Tinospora cordifolia, Justicia adhatoda, Solanum virginianum and Trichosanthes dioica. In this study, estimations of the phenolic, flavonoids and tannin contents, HPTLC profile and in vitro anti-oxidant and anti-microbial potential of 3 extracts of the Panchatikta were carried out. The total phenolic content of the Panchatikta combination was almost the same in ethanol, water and hydroalcoholic extracts. Flavonoid content and tannin content were highest in ethanol extract. HPTLC profiling of the 3 extracts of Panchatikta showed the maximum number of peaks for the ethanolic extract. Water extract showed a comparatively smaller number of peaks. The maximum number of peaks was seen after derivatisation. In the DPPH assay, gallic acid has IC50 value of 5.50 ± 0.38 µg/mL; ethanol and hydroalcoholic extracts have IC50 close to 60 µg/mL and water extract has around 90 µg/mL. The ABTS assay showed standard ascorbic acid has a IC50 value of 67.33 ± 0.58 µg/mL while Panchatikta extracts have a much higher IC50. In nitric oxide assay also, tested samples have a higher IC50 when compared with that of ascorbic acid (177.33 ± 5.09). In well diffusion assay for antibacterial screening, all 3 extracts have a significant zone of inhibition at concentrations of 500 µg and 1000 µg. Pseudomonas aeruginosa was found to be resistant to all 3 test samples and standard antibiotic discs. Minimum activity was obtained against Klebsiella pneumonia. Panchatikta extracts at concentrations of 500 µg and 1000 µg showed significant activity against the fungal strains Aspergillus niger and Fusarium oxysporum. In conclusion, the results of the study can provide scientific support for the traditional usage of the Ayurvedic drug combination Panchatikta for various ailments.